(untitled) (Eurasian Medical Research Periodical, 2022)
Sleep deprivation is a major public health challenge in modern societies. The current study aims to assess the level of sleep deprivation of the nurses in critical care units, reveal the consequences of sleep deprivation, and characterize the relationship between them with the demographic data of nurses. A descriptive design has been performed in the current study. It has been carried out in the critical care units of hospitals in the city of Najaf from October 20, 2021 to March 20, 2022. A Non-probability a technique of (purposive) samples of the (163) nurses in critical care units for night shifts has been selected. Measurement level of sleep deprivation through the sleep deprivation scale modified by expert committee, and the general health status was determined from the General Health Questionnaire (GHQ-28) consisting of (28) items, and it includes four aspects: physical, social, depression, and anxiety. The results of the current study have shown that the level of sleep deprivation is moderate. The results also have revealed that the assessment of most domains (physical, social, and anxiety) was moderate, except for the domain of depression, which was good. There is a significant relationship between sleep deprivation and general health status. It has been concluded that the majority of the nurses showed a moderate level of sleep deprivation and most of them showed a moderate level of general health status.